Peranan Investasi terhadap Penyerapan Tenaga Kerja di Kota Semarang - Reny Yesiana; Khristiana Dwi Astuti; Nanik Setyowati; Jihan Shonia Pardcipta; Inasa Rifdatul Izzati Lillah; Gilang Ardi Pradana (Jurnal Riptek, 2022)
Investment is an activity that can act as a stimulator for the smooth production process. With an increase in capital stock, production capacity and quality will also increase. This will open up opportunities for employment needs. The increase in workers can provide additional income, growing people's per capita income and economic growth. In 2021, Semarang had the most considerable number of workers in Central Java, which was 936,076. This study aims to analyze the role of investment for Semarang City employment. The data collection technique was document review. Those documents were the Semarang Gross Regional Domestic Product by Industry 2017–2022 from Statistics of Semarang Municipality, the Central Java Gross Regional Domestic Product by Regency/City from Statistics of Central Java, the Recapitulation of Realization of Semarang Capital Investment in 2017–2021 from the Semarang One-Stop Integrated Service and Investment Services, and the Population-Based Employment Report in 2017–2021 from the Semarang Civil Registry Office. The research methods used are quantitative by calculating the investment ratio to employment. The results show that the "Manufacturing" sector has the highest job. Meanwhile, the workforce in the "Electricity & Gas" and "Water supply, Sewerage, Waste Management & Remediation Activities" sectors are still low. Therefore, the government should pay close attention to these sectors because they have great job opportunities.